Construction of digital twin application platform for regional multi-energy system - Tang Xueyong; Yao Junrong; Wan Huijiang; Li Zhen; Yang He (Dianzi Jishu Yingyong)
For the status quo of lack of high-performance platforms that support the access, management and operation of upper-layer applications such as dynamic planning and operation optimization of digital twins in regional multi-energy systems, this paper takes into account the requirements of digital twin applications for communication efficiency and data security, with the help of CloudPSS cloud simulation platform, the software and hardware of a secure, flexible, and scalable digital twin application platform including the basic layer, application layer, and business layer are designed. Taking Guizhou Hongfeng Lake regional multi-energy system as the pilot area, it introduced the construction process of the regional multi-energy system digital twin application platform including modeling and simulation, data communication and application integration functions. The built regional multi-energy system digital twin application platform serves as an ideal tool for realizing digital twins from concept to application, its architecture design plan and specific construction experience can provide theoretical and practical references for the wide implementation of digital twin technology.